1970
DOI: 10.1111/j.1467-9485.1970.tb00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth Areas, Growth Centres and Regional Conversion*

Abstract: Summary Five arguments in favour of a growth area strategy have been analysed and though all of them lack empirical substance, they have certain merits on a priori grounds. Thus any policy which contributes, on the long‐run, to a more rapid concentration of a region's population into relatively large urban areas, is likely to create the conditions for servicing net and replacement demand for social/economic overhead capital at a low per capita cost. Moreover for a given subsidy cost, discriminatory investment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1971
1971
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In fact, a similar regularity has attracted recent interest in the context of the growth of cities (see, for example, Clark and Stabler, 1991;and Guérin-Pace, 1995). Differential costs for providing public services may manifest distinct returns to scale in accordance with city size (see, for example, Cameron, 1970). Clark and Stabler (1991) have associated constant economies of size for cities with unit roots in firm size.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a similar regularity has attracted recent interest in the context of the growth of cities (see, for example, Clark and Stabler, 1991;and Guérin-Pace, 1995). Differential costs for providing public services may manifest distinct returns to scale in accordance with city size (see, for example, Cameron, 1970). Clark and Stabler (1991) have associated constant economies of size for cities with unit roots in firm size.…”
Section: Introductionmentioning
confidence: 99%
“…But even in detailed studies for OIAs the structural component is weaker than expected: Cameron (1970) in his study of the Clydeside region suggested that the high locational component called for further explanation. The negative structural concentration may be the starting point for an analysis, and it can influence further factors which are important for growth, but it cannot be regarded as the reason for slow growth.…”
Section: Structurementioning
confidence: 90%
“…The theory just outlined has implications for the spatial distribution of water and other public investments designed to accelerate regional economic growth. The growth center strategy for regional development has attracted wide interest among economists [e.g., Hansen, 1969Hansen, , 1971Hansen, , 1972Cameron, 1970;Robinson, 1969] Although Alonso [1971, p. 70] is probably correct when he says that the existing growth center theory 'hovers somewhere between intuition and poetry,' there appears to be a consensus among economists that, in general, cities below 25,000 population offer little or no promise of the self-sustained growth necessary to provide the migration alternative or spread effects that are policy objectives. The growth center must be large enough to provide an efficient infrastructure and to allow and promote the growth of external economies, which are necessary for the city to capture a growing share of the nation's employment.…”
Section: Implications For Regional Development Strategymentioning
confidence: 99%